Capacity credit estimation for solar PV installations in conventional generation: impacts with and without battery storage. Issue 22 (17th November 2021) - Prajapati, Sandhya; Fernandez, E.
ABSTRACT: In this paper, an attempt is made to estimate the capacity credit of solar PV generation involves two cases, namely, a solar PV system without battery storage and solar PV systems with battery backup. The analysis has been applied to the IEEE Reliability Test System (RTS). The state duration approach, along with appropriate reliability indices is used for capacity credit estimation. The results indicate that the improvement in capacity credit is significantly high for the battery storage range considered (0-18MWh) as compared to the solar PV installation addition range (100-1000MW). The findings of this study can help in evaluating the scope of solar PV penetration in conventional generation-based systems. Thus can be utilized by power system planners interested in harnessing benefits of renewable energy.